Infeksi Alamiah Toxocara vitulorum pada anak sapi perah di Bayong bong, Garut - Simon He; Syahril H. (Hemera Zoa, 1992)
One hundred and two diary calves of 1-12 montha old at Bayonghong, Garut, West Java were examined  for toxacara vitulorum eggs in their feces.